Laser Technology of Optical Meta-Materials - D. Volpyan, O.; I. Kuzmichev, A.; A. Obod, Yu.; S. Sigov, A. (International Journal of Engineering and Technology, 2018)
The basic methods of laser technology used to obtain 2D and 3D meta-materials are considered. The main attention is paid to the methods of forming submicron and nanometer structures using the two-photon polymerization effect and various types of laser interference lithography. It is shown that these technological methods, being planar and scalable, are promising for use in industrial optical production due to their potentially high productivity and low cost compared to many other methods of nanotechnology, in particular, with electronic lithography and processing with focused ion beams.Â Â